Does the Employability Paradox Exist or Not? An Inverted U-Shaped Model - Yu, Haibo; Yan, Changli; Zhang, Lu; Dong, Zhenhua; Cheng, Long; Zheng, Xiaoming; Zhao, Ziqian (Frontiers in Psychology, 2021)
This paper’s purpose is to test the employability paradox by adopting a combined linear and nonlinear approach based on the conservation of resource (COR) theory and the prospect theory and further to discuss it in two groups of employees with different seniority following the career timetable perspective. A total of 623 pairs of matched employee and manager surveys was collected from 27 Chinese enterprises in two waves. Hierarchical regression analysis was used to test the hypotheses. The results show no paradox that perceived employability promotes both an employee’s turnover intention and performance. Specifically, perceived employability has a significant inverted U-shaped effect on turnover intention but no direct influence on job performance. Seniority is a moderator, showing the curvilinear relationship only exhibits for employees with shorter work seniority (≤ 3 years), and a positive linear relationship between perceived employability and job performance only exists for employees with longer seniority (>3 years). This study emphasizes the value of employability for employers and proposes who is more suitable and what timetable should be followed for employability enhancement in practice. In addition, the study provides an enlightening finding of the inverted U-shaped relationship between perceived employability and turnover intention, applies the COR theory and the prospect theory to explain the nonlinear relationship, validates the effect of too much of a good thing (TMGT), and negates the paradox from the perspective of the perceived general employability and career timetable.